2019
DOI: 10.1039/c9sc01415b
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of supported Ru–Triphos catalysts for continuous flow application in selective nitrile reduction

Abstract: Selectivity of immobilized Triphos-type catalysts can be tuned for application in nitrile hydrogenation in batch and continuous flow processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Kamer and co-workers 85 reported the polymer supported Ru-triphos complex for the hydrogenation of nitriles to amines. Initially, the resin-bound phosphine dichloride was prepared by deprotonation using an excess of LDA (lithiumdiisopropylamide) with 1,1,1-tris(chloromethyl)ethane.…”
Section: Supported Metal Complex-based Catalysts For Organic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Kamer and co-workers 85 reported the polymer supported Ru-triphos complex for the hydrogenation of nitriles to amines. Initially, the resin-bound phosphine dichloride was prepared by deprotonation using an excess of LDA (lithiumdiisopropylamide) with 1,1,1-tris(chloromethyl)ethane.…”
Section: Supported Metal Complex-based Catalysts For Organic Synthesismentioning
confidence: 99%
“…However, a loss in the activity was observed in the fourth cycle under batch conditions, and this is due to the mechanical abrasion of the support. 85…”
Section: Supported Metal Complex-based Catalysts For Organic Synthesismentioning
confidence: 99%
“…[30] The development of functional inorganic-organic supramolecular materials and the immobilization of suitable guest complexes on solid surfaces have been extensively investigated. [31,32] Both steric and electrostatic constraints can change the structure and reactivity of the guest complexes, which frequently leads to unexpected physicochemical characteristics in comparison with their properties in solution. [33][34][35] Among various inorganic host materials, ZrP, as a family of transition metal phosphate materials, increasingly attracts research interest due to its outstanding physical and chemical properties, including an extremely high ion-exchange capability and excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ru is widely used as an active element in the hydrogenation reactions, its application in continuous flow process is rarely reported [35,37,40,41]. Moreover, it was reported that in nitro group reduction Ru shows higher selectivity to the desired halogenated anilines than the more active Pt or Pd [38].…”
Section: Introductionmentioning
confidence: 99%